The efficacy of gemcitabine and docetaxel chemotherapy for the treatment of relapsed and refractory osteosarcoma: A systematic review and pre‐clinical study - Kaan Low; Paola Foulkes; Frank Hills; Helen C. Roberts; Britta Stordal (Cancer Medicine)
Abstract Introduction Osteosarcoma is the most common primary malignancy of the bone. There is a lack of effective treatments for patients who experience relapsed osteosarcoma. One treatment for relapsed patients is gemcitabine and docetaxel combination chemotherapy (GEMDOX). This systematic review aimed to establish the efficacy of this chemotherapy regimen, as well as identify the common severe toxicities that are associated with it. Resistant osteosarcoma cell lines developed from MG‐63 and HOS‐143B were used to represent relapsed osteosarcoma patients in a pre‐clinical study. Results We identified 11 retrospective and Phase II studies that were suitable for inclusion in our review. 10.65% of patients had a response to gemcitabine and docetaxel combination therapy and the disease control rate was 35% (n = 197). 36%, 35.3% and 18.04% of patients experienced grade 3 or 4 neutropenia, thrombocytopenia and anaemia respectively (n = 133). Male patients (X2 = 9.14, p < 0.05) and those below the age of 18 (X 2 = 10.94, p < 0.05) responded better to GEMDOX treatment than females and patients older than 18 years. The resistant osteosarcoma cell lines remained sensitive to either single‐agent gemcitabine, docetaxel, and the combination of both. Cisplatin‐resistant models (MG‐63/CISR8 & HOS‐143B/CISR8) were the most responsive to GEMDOX treatment compared to doxorubicin, methotrexate, and triple‐combination resistant models. Conclusion GEMDOX treatment has potential efficacy in relapsed osteosarcoma patients especially those with cisplatin resistance. To directly compare the efficacy of GEMDOX therapy against other therapies randomised phase III clinical trials with adequate patient follow up must be performed to improve treatment options for osteosarcoma.